The Russian Cinema Reader : Contemporary Russian Cinema (2005-2015). - Salys, Rimgaila (Film + media studies., 2019)
This collection surveys recent developments in Russian cinema and introduces undergraduate students to significant films released between 2005 and 2016 that are also available with English subtitles. Essays on individual films provide background on directors' careers, detailed analyses of selected films, along with suggestions for further readings both in English and Russian.